2002
DOI: 10.1002/gcc.10143
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent allelic imbalance at the rat Pten locus in DMBA‐induced fibrosarcomas

Abstract: The tumor-suppressor gene PTEN (phosphatase and tensin homolog) is frequently inactivated in different types of human tumors. Less is known about the involvement of the homologous gene Pten in animal model systems of cancer. By sequencing one of the introns of rat Pten, we found an informative intragenic PCR marker suitable for genetic studies. Through use of this marker, the position of Pten in the genetic linkage map was localized to the distal part of rat chromosome 1 (RNO1) by analysis of F2 progeny from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Taken together, these results suggest that Pten is likely involved in tumorigenesis of BDII rat EAC. Similar conclusions regarding Pten functioning in a Endocrine-Related Cancer (2009) 16 99-111 www.endocrinology-journals.org haploinsufficient mode has been drawn in several other reports (Di Cristofano et al 1998, Kwabi-Addo et al 2001, Sjöling et al 2002, Kolasa et al 2006, Kwon et al 2008. Decreasing level of PTEN expression was shown to correlate with the progressive outcome of solid cancers, including ovarian, prostate, and cervical cancers (Harima et al 2001, Jiang & Liu 2008.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Taken together, these results suggest that Pten is likely involved in tumorigenesis of BDII rat EAC. Similar conclusions regarding Pten functioning in a Endocrine-Related Cancer (2009) 16 99-111 www.endocrinology-journals.org haploinsufficient mode has been drawn in several other reports (Di Cristofano et al 1998, Kwabi-Addo et al 2001, Sjöling et al 2002, Kolasa et al 2006, Kwon et al 2008. Decreasing level of PTEN expression was shown to correlate with the progressive outcome of solid cancers, including ovarian, prostate, and cervical cancers (Harima et al 2001, Jiang & Liu 2008.…”
Section: Discussionsupporting
confidence: 74%
“…The Pten intragenic marker D1Lev1 (Sjöling et al 2002) is informative between the BDII and SPRD strain animals, but not between BDII and BN rats. The D1Lev1 marker was used in conjunction with another informative microsatellite marker (D1Rat81) for AI scoring of Pten locus in animals of the SPRD cross.…”
Section: Allelic Imbalance Analysis and Mutation Sequencing Of The Ptmentioning
confidence: 98%
“…In this study, we demonstrated that the PTEN mutation in STS in Chinese patients, at a frequency of 2.3%, is rare. Their mutation frequency and distribution were consistent with previous reports (22,29,30). In this study, we used PCR-SSCP and DNA sequencing techniques to investigate the sequences of exons 5-8, which were frequently mutated in 86 STS cases.…”
Section: Discussionsupporting
confidence: 87%
“…Although loss of one functional Pten allele was found in 68% of prostate tumors from Pten þ /À mice and in 47.4% of tumors from wild-type mice, no evidence for any specific intragenic mutations was found in any of these tumors. To our knowledge, no examples exist of intragenic mutations in any mouse (Kwabi-Addo et al, 1998) or rat (Sjoling et al, 2003) models involving LOH at the Pten locus. The situation we have seen in mouse lymphomas more closely resembles that seen in human tumors, in that we see a proportion of small localized changes within the Pten gene, but in only rare cases are these homozygous.…”
Section: Discussionmentioning
confidence: 99%